Pengaruh Dosis Limbah Biogas Sapi terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomea reptans Poir.) Varietas Rajawali dan Ta Fung - Ahmad Kusaeri Hidayat; R Wahyono Widodo; Odang Hidayat (OrchidAgro, 2021)
This experiment aims to study the interaction and find the dosage of cow biogas waste that gives the best effect on the growth and yield of ground spinach plants of Rajawali and Ta Fung varieties. This experiment was carried out from July to September 2020, in the experimental garden of the Faculty of Agriculture, Winaya Mukti Tanjungsari University, Sumedang Regency. The experimental design used was the Split Plot Design which consisted of 10 treatments and 3 replications. The treatment consisted of 2 levels, namely the main plot in the form of Rajawali variety and Ta Fung variety, while the sub plot was in the form of a dose of cow biogas waste consisting of 0 tons. Ha-1, 5 tons.ha-1, 10 tons.ha-1, 15 tons. ha-1 and 20 ton.ha-1. The results of this experiment showed that there was no interaction between variety and cow biogas waste on all observed parameters, independently Variety had an effect on plant height at the age of 14 day after planting while cow biogas waste had an effect on fresh weight per plant and fresh weight per plot. Ta Fung variety gave the best plant height at 14 day after planting, while cow biogas waste with a dose of 15 tonnes.ha-1 gave the best fresh weight per plant and fresh weight per plot.